2009
DOI: 10.1177/1352458509106213
|View full text |Cite
|
Sign up to set email alerts
|

Subjective fatigue is not associated with cognitive impairment in multiple sclerosis: cross-sectional and longitudinal analysis

Abstract: We conclude that self-reported fatigue, while correlated with self-reported depression, is not significantly related to cognitive capacity in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 55 publications
(87 reference statements)
9
39
3
3
Order By: Relevance
“…Similar to previous research, 27 significant differences in SDMT performance were found between fatigued and nonfatigued persons with MS. The present results differ from past literature, however, such that fewer domains were found to be associated with depressive symptoms.…”
Section: Practice Pointssupporting
confidence: 90%
“…Similar to previous research, 27 significant differences in SDMT performance were found between fatigued and nonfatigued persons with MS. The present results differ from past literature, however, such that fewer domains were found to be associated with depressive symptoms.…”
Section: Practice Pointssupporting
confidence: 90%
“…Furthermore, our study consisted of two MS groups (MSF and MS0) and controls, whereas several previous studies only used one MS group, for which they determined the mean fatigue score [4,6,12,13,16,17,19,20,30].…”
Section: Discussionmentioning
confidence: 99%
“…Both can have implications for all aspects of daily life, and are often not recognized promptly. Several studies have investigated the relationship between fatigue and cognition, but could not find a significant correlation [4,5]; however, deficits in reaction time and processing speed have been associated with fatigue [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…This hypothesis is supported by a recent study showing that MS patients' self-rankings on the Beck Depression Inventory Fast Screen were moderately correlated with rankings on the Fatigue Severity Scale, but not with cognitive results from formal neuropsychological testing. 27 Pain may also be more influential on perceptions of fatigue than on performance measures. However, the PVT is a simple task and it is possible that with a more complex, multi-step task these factors would be associated with a decline in performance.…”
Section: Discussionmentioning
confidence: 99%